Co-Creation as a Tool to Overcome Cross-Cultural Differences in Educational Experiences?. Issue 3 (2nd July 2020) - Vespestad, May Kristin; Smørvik, Kjersti Karijord
ABSTRACT: The teaching-learning relationship has been subject to discussion within higher education (HE), as has the traditional lecture. Teaching and lectures cannot be understood without including students as part of the setting, particularly so within a cross-cultural classroom where various hermeneutics are involved. International students have different ways of understanding and interpreting data, and may be accustomed to various educational traditions. The aim of this study is to discuss how co-creation can function as a tool for overcoming differences within a cross-cultural context. Qualitative empirical data were collected in four different tourism and marketing student groups. The study findings show that despite requiring increased effort and commitment from all stakeholders, co-creation principles do contribute to bringing about valuable educational experiences. The study contributes to generating a new mind-set that can promote valuable learning experiences. It furthermore endorses co-creation as an approach that can enhance value outcomes in a cross-cultural context.